2019
DOI: 10.2151/jmsj.2019-065
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coastal Convection to Moisture Buildup during the South China Sea Summer Monsoon Onset

Abstract: In this study, the climatological characteristics of object-based precipitation systems (OPSs) and moisture development are analyzed over the South China Sea (SCS) during the sharp transition of the summer monsoon onset. The satellite-observed statistics of the OPSs showed that over the 20-day pre-onset period, OPSs of small (< 100 km) to medium size (100-300 km) are active over the lands surrounding the SCS. The pre-onset composite mean shows a basin-scale (~ 1000 km) local circulation with anomalous subsiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Recent studies have found that the cloud vertical structure and the associated diabatic heating are tightly connected to the modulation of the large‐scale environment during the transition of intraseasonal variability (e.g., Ciesielski et al., 2017; Del Genio et al., 2012; DelGenio & Chen, 2015; Hung et al., 2020; Riley et al., 2011) and monsoon onset (e.g., Chen, Wu, & Ma, 2019a, Chen, Wu, Tsai et al., 2019b). In the future, collocating the other satellite products from the A‐train, the Global Precipitation Measurement, or the geostationary Himawari‐8 / 9 satellites can be carried out to provide additional properties to the convective systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that the cloud vertical structure and the associated diabatic heating are tightly connected to the modulation of the large‐scale environment during the transition of intraseasonal variability (e.g., Ciesielski et al., 2017; Del Genio et al., 2012; DelGenio & Chen, 2015; Hung et al., 2020; Riley et al., 2011) and monsoon onset (e.g., Chen, Wu, & Ma, 2019a, Chen, Wu, Tsai et al., 2019b). In the future, collocating the other satellite products from the A‐train, the Global Precipitation Measurement, or the geostationary Himawari‐8 / 9 satellites can be carried out to provide additional properties to the convective systems.…”
Section: Discussionmentioning
confidence: 99%
“…CloudSat cloud mask observations were first processed by the 4‐way connection to identify cloud objects (Chen, Wu, Tsai et al., 2019; Tsai & Wu, 2017; Su et al., 2019). The connecting algorithm is provided in the supporting material .…”
Section: Methodsmentioning
confidence: 99%
“…[2008]), the land surface model (Noah LSM, F. Chen & Dudhia [2001]), the first‐order turbulence closure (Shutts & Gray, 1994), the predicted particle properties microphysical scheme (Huang & Wu, 2020; Morrison & Milbrandt, 2015), and the block topography (Chien & Wu, 2016; Wu & Arakawa, 2011) has been implemented in the VVM for studying complicated interactions associated with convection, such as the unified parameterization of deep convection (Arakawa & Wu, 2013; Wu & Arakawa, 2014), stratocumulus transition (Tsai & Wu, 2016), the aggregated deep convection (Tsai & Wu, 2017), afternoon thunderstorms (Kuo & Wu, 2019), land‐atmosphere interactions (Wu et al., 2015, 2019; Wu & Chen, 2021), cloud‐aerosol interactions (Chang et al., 2021), and the coastal convection during summer monsoon onset (W.‐T. Chen et al., 2019).…”
Section: Model Description Experimental Settings and Analyses Methodsmentioning
confidence: 99%